Factor structure and psychometric properties of the Connor Davidson resilience scale among Brazilian adult patie - Solano, João Paulo Consentino; Bracher, Eduardo Sawaya Botelho; Faisal-Cury, Alexandre; Ashmawi, Hazem Adel; Carmona, Maria José Carvalho; Neto, Francisco Lotufo; Vieira, Joaquim Edson (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: Personal resilience is associated with several mental health outcomes. The Connor-Davidson resilience scale (CD-RISC) is a widely used self-report measurement of resilience. This study aimed to investigate the reliability and validity of a Brazilian Portuguese version of the CD-RISC. DESIGN AND SETTING: Cross-sectional validation study carried out in the outpatient clinics of a public university hospital. METHODS: The cross-cultural adaptation followed established guidelines and involved interviews with 65 adults in psychiatric and non-psychiatric outpatient clinics at a teaching hospital. Validation was assessed through concurrent application of the Lipp Brazilian Stress Symptom Inventory (ISSL), Self-Report Questionnaire (SRQ), Sheehan Disability Scales (SDS) and Chronic Pain Grade (CPG) to 575 patients at the same setting. Temporal stability was verified through a second application to 123 participants. RESULTS: Factor analysis identified four factors, named tenacity, adaptability-tolerance, reliance on support from outside and intuition. The alpha coefficient of 0.93 and intraclass correlation coefficient of 0.84 indicated good internal consistency and temporal stability. Significant correlations between this version of the CD-RISC and the ISSL, SRQ, SDS and CPG were noted. The patients at the outpatient clinic for borderline personality had resilience scores that were significantly lower than those of the patients at the general anxiety or post-traumatic stress outpatient clinics. CONCLUSION: This Brazilian Portuguese version of the Connor-Davidson resilience scale exhibited adequate reliability and validity among a sample of Brazilian adult patients.